Prediction of pregnancy in artificial reproductive techniques through evaluation of thickness, morphology and vascularity of endometrium - Misra, Aditya Prakash; Mishra, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prediction of pregnancy in Artificial Reproductive Techniques through evaluation of thickness, morphology and vascularity of endometrium. Methods: Endometrial thickness, morphology and sub endometrial blood flow were assessed using trans-vaginal ultrasound on the day of HCG in 200 undergoing IVF/ICSI treatment in the period between October 2009 and December 2014. Statistical analysis was done. Results: There was no difference in the demographic features between pregnant and non-pregnant women. Overall, 80 patients conceived; 46 (57.5%) of them had blood flow in zone III and 30 (37.5%) in zone II. All patients achieved pregnancy had endometrial thickness >8 mm. There was no significant difference in Doppler indices between pregnant and non-pregnant women. Conclusions: When the endometrial thickness is <8 mm, and if there are non-triple endometrial line, pregnancy rate decreases and the absence of colour mapping of the endometrium and subendometrial areas means and absolute implantation failure or a significant decrease of the implantation rate. Conversely, the pregnancy rate increases when the vessels reach endometrium.